Some Patterns and Processes of Women's Faith Development - Slee, Nicola (Journal of beliefs and values, 2000)
Drawing on Fowler's faith development theory and feminist theological and psychological studies of women's faith, as well as feminist research principles, open-ended interviews were used to explore the faith lives of 30 Christian or post-Christian women. Findings are presented in terms of two main categories. First, six processes of faithing are identified: these are strategies by which the women discerned and embodied shape, pattern and meaning in their life experience. Second, three major generative themes are identified which, it is suggested, represent key patterns in the women's faith. The three themes of paralysis, awakenings and relationality are described and discussed. The findings challenge Fowler's claim to provide a normative account of faith development, and reveal aspects of women's experience which require fuller attention in future research.